Linguistic And Grammatical On Ithbat al-Muhsal By Ibn al-Mustawfi/ اللغة والنحو في إثبات المحصل لابن المستوفي - Alhajj Ebrahim, Abdullah Omar; Alzahrani, Mohamed Jarallah Ahmed (Ijaz Arabi Journal of Arabic Learning, 2025)
Scholars from various backgrounds have dedicated their lives to knowledge and enriching this Arab Islamic civilization with outstanding works. Among these figures is one of the notable scholars of the seventh century AH, namely Ibn Al-Mustawfi, Al-Mubarak Ibn Ahmad Ibn Mawhub, who passed away in 637 AH. This research pertains to this great personality and seeks the virtues of this linguistic, grammatical, historical, and rhetorical scholar, as well as the characteristics of his book. It also highlights some linguistic and scientific phenomena found in the book. The methods used in this study are descriptive, inductive, and analytical methods. The study results show that Ibn al-Mustawfi was a grammarian, linguist, rhetorician, and historian, as evidenced by the legacy he left us, covering all of these fields. The most important characteristic of this book is that its author explains many of the words of the author of the book, Al-Mufassal, and the benefits of this book include explanations of the evidence. As for the linguistic and scientific phenomena found in this book, the most prominent ones are linguistic reports and grammatical discussions with previous scholars.